Perspectives on teaching language and content - Bourns, Stacey Katz, 1963-; Krueger, Cheryl; Mills, Nicole (Yale University Press, 2020)
An overview of current issues and developments in foreign language education, designed for instructors of language, literature, and culture at any stage of their careers. A contemporary guide to foreign language education, this book presents the latest developments and issues in the field of applied linguistics. It leads instructors to make vital connections between theory and practice and to develop innovative lesson plans, classroom activities, and course materials that align with the specific contexts in which they teach. A textbook for teaching methods courses, as well as a reference for instructors of language, literature, and culture at any stage in their careers, the book is applicable across all lower- and upper-level courses.